2021
DOI: 10.1186/s12984-021-00964-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pelvic movements of a gait training system for stroke patients: a single blind, randomized, parallel study

Abstract: Background Aging societies lead to higher demand for gait rehabilitation as age-related neurological disorders such as stroke and spinal cord injury increase. Since conventional methods for gait rehabilitation are physically and economically burdensome, robotic gait training systems have been studied and commercialized, many of which provided movements confined in the sagittal plane. For better outcomes of gait rehabilitation with more natural gait patterns, however, it is desirable to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…This is thought to be related to a previous study, which found that lateral and rotational pelvic movements of Healbot T increased voluntary muscle activation, cadence, and walking speed. [17] Furthermore, Veneman et al suggested that pelvis fixation should be avoided and demonstrated that pelvis fixation in the horizontal plane during treadmill walking severely affects gait dynamics. [33] A previous study found that the FreeD module of Lokomat (Hocoma AG, Switzerland), which guides lateral translation and transverse pelvic rotation, promoted physiological movement patterns in the trunk and hip during gait in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is thought to be related to a previous study, which found that lateral and rotational pelvic movements of Healbot T increased voluntary muscle activation, cadence, and walking speed. [17] Furthermore, Veneman et al suggested that pelvis fixation should be avoided and demonstrated that pelvis fixation in the horizontal plane during treadmill walking severely affects gait dynamics. [33] A previous study found that the FreeD module of Lokomat (Hocoma AG, Switzerland), which guides lateral translation and transverse pelvic rotation, promoted physiological movement patterns in the trunk and hip during gait in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A previous paper on some data from this study had been published. [17] This study was about a secondary analysis of collected data.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…1.f) were later introduced, and they were useful for generating stable levels of cable tension. However, there is growing evidence that constantly unloading part of the body weight may limit several joint motions including lateral and transverse pelvic movement, which are two of the six determinants of the natural gait [20]. Moreover, the duration of the user's stance and double-limb support may be decreased under relatively higher levels of BWS, which suggests that BWS can stimulate shorter periods of foot contact.…”
Section: Introductionmentioning
confidence: 99%
“…Since pelvis motion plays a critical role in serving an optimal center of mass movement, producing smooth and energetically efficient overground gait locomotion [20], monitoring and supporting the user's pelvis movement simultaneously under partial BWS becomes essential [38]. To look into pelvis movement in more detail, in this research, we utilized the center of mass (CoM) model to represent human walking, and investigate the pelvis motion within the transverse plane.…”
Section: Introductionmentioning
confidence: 99%